PRIMARY PERITONITIS WITH POCKETED ABSCESS INTRAPERITONEAL CAUSED BY UMBILICAL CATHETER INFECTION IN 22 DAYS OLD BABY - -, Ariputra; Kardana, I Made; Darmajaya, Made (Medicina, 2014)
Primary peritonitis defined as a microbial infection of the peritoneum and peritoneal fluid in theabsence of a gastrointestinal or visceral perforation. The source of infection is extra abdominal andmay arise from lymphatics or blood stream. One of the infection source can be extension from anomphalitis or infected umbilicus. Omphalitis can occur due to complication of Umbilical VeinCatheterization (UVC). UVC are used to provide access for resuscitation, frequent monitoring ofblood, administration of fluids, blood and parenteral nutrition. We report a case of primary peritonitiswith pocketed intraperitoneal abscess caused by umbilical infection in 22 days old baby. Patientpresent a clinical sign of peritonitis and severe omphalitis with history of using umbilical catheter. X-ray found a free fluid impression in the abdominal cavity. Patient undergo a laparotomy and pocketedintraperitoneal abscess was found around ligamentum teres hepatis area, suspected of infectiouscomplications arising out from the use of umbilical catheter. [MEDICINA 2014;45:193-198].